Europe and the politics of capabilities / edited by Robert Salais and Robert Villeneuve. - Salais, Robert; Villeneuve, Robert, 1943- (Cambridge University Press, 2004)
The social agenda of the European Union is shifting towards broad social initiatives that align social and economic objectives with the promotion of employment. This calls for an action framework that permits social dialogue and political deliberation to inform and complement legislative action at all levels. The debate, however, has been dominated by advocates of traditional welfare states. This book, to break out of this sterile stalemate, demonstrates how an employment-orientated social policy in Europe can develop from a new, different set of policy principles, specifically 'a capability approach'. Taking inspiration from the work of Amartya Sen, this book focuses on the effective freedom people need to achieve their goals in life and work. The result of ongoing collaboration between researchers and social actors, it will appeal to social scientists, students, policy-makers and all those concerned with the building of Europe.